Prevalence of Extended Spectrum Beta-Lactamase Producing Escherichia coli and Klebsiella species from Urinary Specimens of Children attending Friendship International Children’s Hospital - Rimal, Ujjwal; Thapa, Shovana; Maharjan, Roshani (Nepal Journal of Biotechnology, 2017)
Extended-spectrum β-lactamase producing E. coli and K. pneumoniae is a serious threat to the patients. These organisms are major extended spectrum beta lactamase (ESBL) producers. The objective of this study was to determine the prevalence of Extended spectrum β- lactamase producing strains of Escherichia coli and Klebsiella spp isolates from the urine sample of children visiting International Friendship Children Hospital. During the seven months, between June 2016 to December 2016, 1018 mid-stream urine samples(MSU) were collected from patients suspected of having UTI. The samples were investigated by conventional semi-quantitative culture technique and identification of E. coli and Klebsiella spp. was done by microscopy and biochemical test. Antibiotic susceptibility test of isolates was performed by modified Kirby Bauer Disc diffusion test. ESBL screening test was done by using 3rd generation Cephalosporin and confirmation done by combination disc diffusion method. Out of total 1018 MSU samples investigated, 200(19.64%) isolates of E. coli and 28(2.7%) isolates of Klebsiella spp. making a total of 228(22.39%) were found to cause significant bacteriuria. 76(33.33%) isolates, from those causing significant bacteriuria, were Multi-drug resistant organisms. Out of 228 isolates, 54(23.68%) were ESBL producers, that includes 51(25.5%) Escherichia coli and 3(12.5%) Klebsiella pneumoniae. ESBL producers were more common in in-patient (36.17%) than out-patient (20.44%). Most of the ESBL producers were resistance to amoxicillin, followed by Cotrimoxazole and Ciprofloxacin respectively. They were highly sensitive to Imipenem, Tigecycline, Amikacin, Piperacillin-Tazobactam, and Nitrofurantoin. High prevalence of ESBL producing E. coli and Klebsiella pneumoniae was found among children. Regular and routine monitoring of ESBL producing isolates is essential. Nepal Journal of Biotechnology. Dec. 2017 Vol. 5, No. 1: 32-38